Penerapan Asas-Asas Penyelenggaraan Pemerintahan Yang Baik Ditinjau dari Undang-Undang Nomor 32 Tahun 2004 - Devi Supusepa (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This study aims to determine the implementation of good governance, especially in Yahukimo Regency according to Law No. 32 of 2004, and to find out the obstacles faced by the Yahukimo Government in establishing good governance. The research method used was empirical juridical research method which was carried out to find and obtain data directly in the field according to the problems studied. Data were obtained through observation, interviews, and document studies. The results of the study indicate that the application of good governance, especially in the procurement of goods and services, in Yahukimo is generally guided by Law No. 32 of 2004 and Presidential Decree No. 80 of 2003 on guidelines for the implementation of the procurement. Obstacles in the procurement do not fully meet the expectations of good governance, it is caused by: (1) that legislation as a guideline for the procurement does not regulate clearly; (2) The institution that specifically handles policy development, guidance and control of the procurement has not been established; (3) Quality and quantity of Human Resources; (4) Information and technology facilities and infrastructure have not been able to support the procurement.